Potential of Microbial Diversity of Coastal Sand Dunes: Need for Exploration in Odisha Coast of India - Shubhransu Nayak; Satyaranjan Behera; Prasad Kumar Dash (The Scientific World Journal)
Coastal sand dunes are hips and strips formed by sand particles which are eroded and ground rock, derived from terrestrial and oceanic sources. This is considered as a specialized ecosystem characterized by conditions which are hostile for life forms like high salt, low moisture, and low organic matter content. However, dunes are also inhabited by diverse groups of flora, fauna, and microorganisms specifically adapted to these situations. Microbial groups like fungi, bacteria, and actinobacteria are quite abundant in the rhizosphere, phyllosphere, and inside plants which are very much essential for the integration of dunes. Microorganisms in this ecosystem have been found to produce a number of bioactive metabolites which are of great importance to agriculture and industries. Many species of arbuscular mycorrhizal fungi and Rhizobia associated with the roots of dune flora are prolific producers of plant growth promoting biochemicals like indole acetic acid. In addition to that bacteria belonging to Pseudomonas sp., Gammaproteobacteria have been found to have antagonistic activity towards plant pathogens like Rhizoctonia solani, Pythium ultimum, Fusarium oxysporum, and Botrytis cinerea. Many neutrophilic and alkaliphilic eubacterial species, endophytic fungi from dunes have proved their ability for the production of extracellular enzymes like cellulase, pectinase, amylase, protease, tannase, chitinase, etc., which are of great importance to various industries. In this context, it is relevant to observe that the state of Odisha in India has a 480km long coast having numerous sand dunes. These dunes are rich in floral and faunal diversity. However, a comprehensive study is yet to be taken up to explore the microbial diversity and their bioactive potential in this region. The current review sheds light on the enormous potential of sand dune microorganisms in the coast and surfaced the idea and need for such exploration in the state of Odisha, India.